Software architecture with C# 10 and .NET 6 : develop software solutions using microservices, DevOps, EF Core, and design patterns for Azure /: develop software solutions using microservices, DevOps, EF Core, and design patterns for Azure. (2022) - Baptista, Gabriel; Abbruzzese, Francesco
No abstract available